A comparative study of efficacy and safety of intravenous ferric carboxymaltose versus iron sucrose in the treatment of iron deficiency anaemia of pregnancy in a tertiary care hospital - Mahajan, Aakanksha; R. Bhagat, Bawa; Gupta, Shashi; Mahajan, Bhanu; Verma, Manvi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Anaemia is a global public health problem. To optimize iron delivery in pregnancy, new intravenous complexes like Ferric carboxymaltose (FCM) have been developed in the few years. This study aims to compare the efficacy and safety of FCM vs the iron sucrose during pregnancy. Methods: This study was conducted in the Department of Obstetrics and Gynaecology, Shri Maharaja Gulab Singh (S.M.G.S.) Hospital, Government Medical College Jammu, Jammu and Kashmir over a period of 1 year. 100 pregnant females with haemoglobin (Hb) in the range 7-9.9 g/dl between 28 to 36-week gestation, were selected randomly out of which 50 were administered FCM (Group A) and 50 were administered Iron Sucrose (Group B). Hb and serum ferritin were assessed 2 weeks and 4 weeks after treatment and side effects of each drug was studied. Results: The rise in mean Hb level at 2 weeks and 4 weeks in FCM group was significantly higher as compared to Iron Sucrose group (1.09 versus 0.52 g/dl and 1.80 versus 1.09 g/dl, respectively). Similarly, the rise in mean serum ferritin level at 2 weeks and 4 weeks was more in FCM as compared to Iron Sucrose group (144.25 vs 95.84 mcg/L and 121.31 vs 84.46 mcg/L, respectively). The adverse reactions were observed in 30% of patients in FCM group and 48% patients in iron sucrose group. Conclusions: Ferric carboxymaltose was found to be more safe and efficacious as compared to iron sucrose.